Government’s Cash Transfers And School Dropout In Rural Areas - Setyadharma, Andryan (JEJAK: Jurnal Ekonomi dan Kebijakan, 2018)
Indonesia is committed to education but the Government of Indonesia still struggle with dropout problem at upper secondary school level, especially students from rural areas who dropping out of school before graduating. The dropout events can be explained through the demand for education. In 2008 Government of Indonesia introduced Bantuan Siswa Miskin program, the Cash Transfers for Poor Students (recently is known as Kartu Indonesia Pintar), in order to reduce numbers of dropouts. The program is mainly to cover students’ indirect costs and is implicitly used to increase students’ demand for education. The objective of this study is to get better understanding on the impact of government’s cash transfers on rural students’ dropout at upper secondary schools in Central Java Province. Primary data was collected from rural areas in all regencies and cities. The likelihood to drop out is estimated using Probit regressions. There are two main findings in this study. First, the result shows that higher education expenditure is significantly increasing the probability of rural students to drop out. Second, it is evidence that government’s cash transfers significantly diminish the rural students’ likelihood of dropping out. Based on the findings, it is suggested the Government of Indonesia must reduce education costs and the government also should expand the number of cash transfers for poor rural students.